Patients with a Hypoplastic Labrum Achieve Similar Outcomes After Primary Labral Repair in the Treatment of Femoracetablular Impingement Syndrome Compared to Patients with a Normal Labrum. Issue 7 (31st July 2020) - Drager, Justin; Newhouse, Alexander; Chahla, Jorge; Nho, Shane; Rasio, Jonathan
Objectives: A preoperative or intraoperative finding of an acetabular labrum width of <4mm is often cited as an indication for performing primary labral reconstruction over repair in the surgical correction of Femoracetablular Impingement Syndrome (FAIS). The purpose of this study is to compare patient reported clinical outcomes and rates of reaching Minimum Clinical Important Differences (MCID) and Patient Acceptable Symptomatic State (PASS) between patients with a hypoplastic labrum compared to those with a normal labrum width at a minimum 1 year from arthroscopic treatment of FAIS. Methods: Data from consecutive patients who underwent primary hip arthroscopy between November 2015 and July 2018 for the treatment of FAIS were analyzed. Baseline demographic data, preoperative, and minimum 1 year post-operative clinical outcomes including Hip Outcome Score-Activities of Daily Living (HOS-ADL), HOS-Sports Subscale (HOS-SS), modified Harris Hip Score (mHHS), international Hip Outcome Tool 12 questions (iHOT-12), and visual analog scale (VAS) for pain and satisfaction were recorded. The labrum size was documented by the senior surgeon for all patients using the tip of an arthroscopic probe measuring 4mm. Labrum hypoplasia was defined as a labrum width at the 12 o'clock position of <4mm and normal labrum was defined as labrum width between 4 and 7mm. Patients with hypoplastic labrum were matched 1:1 by age and BMI to patients with normal labrum width. All patients underwent arthroscopic labral repair in addition to impingement resection and capsular repair. The groups were further compared after separating by acetabular coverage, in which a Lateral Center Edge Angle of 18-24.9 was considered borderline dysplastic and 25-40 was considered normal. Rates of achieving MCID calculated using a distribution-based method and PASS calculated using an anchor-based method. Results: A total of 360 patients were included in the study with 180 in each of the normal and hypoplastic groups. There was no significant differences seen in 1-year post operative outcome scores or score improvement between the two groups. When examining only borderline dysplastic patients there were no significant differences in outcomes between normal and hypoplastic labrum patients. In the subset with a normal LCEA only post-operative VAS satisfaction (85.5 ± 19.3 vs 78.2 ± 27.4; p=0.050) was significantly higher in the normal labrum patients compared to hypoplastic labrum. Patients with hypoplastic labrum achieved MCID and PASS at the same rate as patients with normal labrum across all outcome measures. Conclusions: Patients with an intraoperative finding of labral hypoplasia achieve 1-year meaningful clinical outcome at the same rate as those with normal labral width following arthroscopic labral repair. These results bring into question the need for primary labral reconstruction in patients with labral hypoplasia with a normal or borderline dysplastic acetabulum.